(untitled) (Comprehensive Journal of Science, 2026)
This study examines the level of satisfaction with academic life at the Higher Institute of Mohammed Jamal Al-Durra for Administrative and Financial Sciences in Janzour, a private institution affiliated with the Ministry of Technical and Vocational Education, with nearly 25 years of experience in technical education. The institute aims to contribute to community development and promote scientific research. The research focuses on evaluating students’ satisfaction with academic life, a key factor in enhancing educational quality and institutional effectiveness. Data were collected using a structured questionnaire consisting of 45 items covering three main domains of satisfaction. The findings revealed that the majority of the study sample were female students (77.1%), aged between 18 and 22 years. Overall, the level of satisfaction with academic life was found to be high. However, satisfaction with the educational environment ranked lowest among the assessed domains. The study highlights the importance of improving the educational environment to further enhance students’ academic experience and overall institutional performance.